Forming Process Product Trunk Profile C+/ Channel Plus On Cold Form Steel Machine - Bayu Wiguna; Dodi Sofyan Arief; Muftil Badri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Research on the C+/ Channel Plus Product Forming Process on Cold Form Steel, is done because of the mildsteel with the new profile shape of C + (Channal Plus). This project purpose to determine the process of formingprofile C+ by considering the limits and tolerances allowed. Determining the forming process is an attempt madeto produce a Channal plus profile by considering the properties of the material, including the physicalproperties, mechanical properties and the formability of the profile material. An analytical approach is anattempt to avoid defects in products in a particular area from the result of forming. Each forming has a varietyof shapes, dimensions and functions. It takes the forming stages to produce light steel rod products ranging frommild steel raw material (coil) to the desired profile type. The result of the forming process is shown in the formof a flower diagram and is loaded in a 2 dimensional engineering drawing using Autodesk Inventor software.Key words: shape, dimension and function